Quality Profile of Remote Areas Elementary Schools - Piter Joko Nugroho; Theo Jhoni Hartanto (STAI Hubbulwathan Duri, 2023)
Not all schools understand the policies and procedures for carrying out the school functions based on SNP, among others, caused by due to the lack of understanding/inability of schools to conduct internal self-evaluations, which will provide the description of the real school quality gaps against the SNP, as well as a basis for reference in preparing the RKS and RKAS. This study aims to describe the quality profile of remote elementary schools (SD) in Kapuas Districts, Central Kalimantan Province, Indonesia. The descriptive study with a qualitative approach was conducted in 6 (six) remote areas in SD. The data sources in this study consisted of 6 (six) principals and the Kapuas Districts Education Office personnel. Through interview techniques, observation, and filling out the e-EDS instrument developed by the researchers referring to the SNP for primary and secondary education, quality data of the remote areas SD was collected; then analyzed using interactive data analysis. The results showed that all of the remote areas SD get a “red report”. This study provides additional evidence that disparity problem of primary education quality in remote areas has not been handled properly by education policy makers in Kapuas Districts and related stakeholders. We recommend to the related parties to “borrowing” policies from other countries that have succeeded to overcoming the problems of remote areas education as a means to carry out lessons learned and redesign policies in the future.